2015
DOI: 10.1016/j.transproceed.2015.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile and Cardiovascular Risk in a Population of Renal Transplant Recipients

Abstract: There is a high prevalence of cardiovascular risk factors in a population of RTRs, and there is increased risk for MACE and death. Accurate risk prediction is important for physician decision support and patient education, promoting improved cardiovascular health of RTRs, and thus prolonging the survival of both patients and graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…While the prevalence of hypertension is between 21% and 26% in the general population, this rate varies between 67% and 86% in patients with ESRD. This is similar to our study data [16,18,19,24].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…While the prevalence of hypertension is between 21% and 26% in the general population, this rate varies between 67% and 86% in patients with ESRD. This is similar to our study data [16,18,19,24].…”
Section: Discussionsupporting
confidence: 93%
“…The age of kidney transplant in patients with ESRD varies between 43-50 years, and 58% -61% of these patients consist of male patients [15][16][17][18][19]. The age of the patients included in our study was found as 49 years in accordance with the literature, and 55% of them were male.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previously, a significant relation was found between cardiovascular risk, which increased similarly to that shown in our study, age, male sex, diabetes mellitus, and smoking habits before and after transplant. 15 We also observed that those who smoked for a long time were more likely to smoke after their surgical procedure.…”
Section: Discussionmentioning
confidence: 51%
“…Pretransplant risk factors for CVEs include conventional demographic (and nonmodifiable) factors, such as age (young age in kidney transplantation and older age in liver transplantation), sex, race, preexisting conditions, such as diabetes, ischemic heart disease, duration of dialysis for kidney transplant recipients, smoking and general patient health (Figure 12). 289,292,313,314 Posttransplant risk factors for CVEs include NODAT, hypertension, impaired glucose tolerance, 288,289,292,315 impaired kidney function 295,316 and posttransplant hyperglycemia (Table 11 and Figure 12). 317,318 In clinical trials and registry studies in kidney transplantation, hypertension shows a strong association with major adverse cardiovascular event (MACE), as well as graft failure and mortality 289 ; increased systolic and pulse pressuremarkers of vascular stiffness-are specifically associated with cardiac death and stroke.…”
Section: Risk Factors For Cves In Kidney and Liver Transplant Recipientsmentioning
confidence: 99%